Legal reform on the dispute resolution mechanism in Islamic banking and finance in Indonesia: issues and challenges - Rasyid, Abdul; Zulhuda, Sonny (2011)
Nearly fifteen years after the establishment of the first Islamic bank Indonesia, a new law was introduced in 2006 that in effect empowers the Religious Court in the country to oversee, hear and decide on disputes relating to matters of Islamic finance and Islamic economics. In its way to the enactment, the Parliament preferred the word ‘Islamic economics’ than the word ‘Islamic banking’ which was initially put in the draft law.